Identification, nucleotide sequence, and characterization of PspF, the transcriptional activator of the Escherichia coli stress-induced psp operon. - Jovanovic, G (1996)
The phage shock protein (psp) operon (pspABCE) of Escherichia coli is strongly induced in response to a variety of stressful conditions or agents such as filamentous phage infection, ethanol treatment, osmotic shock, heat shock, and prolonged incubation in stationary phase. Transcription of the psp operon is driven from a sigma54 promoter and stimulated by integration host factor. We report here the identification of a transcriptional activator gene, designated pspF, which controls expression of the psp operon in E. coli. The pspF gene was identified by random miniTn10-tet transposon mutagenesis. Insertion of the transposon into the pspF gene abolished sigma54-dependent induction of the psp operon. The pspF gene is closely linked to the psp operon and is divergently transcribed from one major and two minor sigma 70 promoters, pspF encodes a 37-kDa protein which belongs to the enhancer-binding protein family of sigma54 transcriptional activators. PspF contains a catalytic domain, which in other sigma54 activators would be the central domain, and a C-terminal DNA-binding domain but entirely lacks an N-terminal regulatory domain and is constitutively active. The insertion mutant pspF::mTn10-tet (pspF877) encodes a truncated protein (PspF delta HTH) that lacks the DNA-binding helix-turn-helix (HTH) motif. Although the central catalytic domain is intact, PspF delta HTH at physiological concentration cannot activate psp expression. In the absence of inducing stimuli, multicopy-plasmid-borne PspF or PspF delta HTH overcomes repression of the psp operon mediated by the negative regulator PspA.